2013
DOI: 10.1164/rccm.201212-2334oc
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Peripheral Blood Mononuclear Cell Depletion in Experimental Human Lung Inflammation

Abstract: These findings do not support a role for circulating human monocytes in the early recruitment of neutrophils during LPS-mediated acute lung inflammation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…It is important to highlight that, despite significant differences in cell surface antigen expression by iPMLC and rPMLC, a degree of heterogeneity exists within both PMLC subpopulations, and it is plausible that functional crossover may occur. We have previously reported differential cell counts from cytocentrifuge preparations of BAL fluid from subjects who have inhaled LPS and then undergone active leukapheresis compared to those receiving sham leukapheresis [1], which was in accordance with the secondary endpoint of our RCT of pulmonary neutrophilia in BAL fluid. A discrepancy exists in the reported cellular composition of BAL fluid when comparing data from cytocentrifuge preparations compared to lineage analysis using polychromatic flow cytometry reported herein.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…It is important to highlight that, despite significant differences in cell surface antigen expression by iPMLC and rPMLC, a degree of heterogeneity exists within both PMLC subpopulations, and it is plausible that functional crossover may occur. We have previously reported differential cell counts from cytocentrifuge preparations of BAL fluid from subjects who have inhaled LPS and then undergone active leukapheresis compared to those receiving sham leukapheresis [1], which was in accordance with the secondary endpoint of our RCT of pulmonary neutrophilia in BAL fluid. A discrepancy exists in the reported cellular composition of BAL fluid when comparing data from cytocentrifuge preparations compared to lineage analysis using polychromatic flow cytometry reported herein.…”
Section: Discussionsupporting
confidence: 73%
“…Details of the RCT including subject demographics are described elsewhere [1]. For this component of the study, healthy male non-smokers aged 18-40 (n = 15) inhaled 60 μg LPS (from Escherichia coli 026:B6, L2654; Sigma, Poole, UK) using an inhalation-synchronised dosimeter nebuliser (Spira Elektro 2, Hameenlinna, Finland) as described [6], and were then randomised to receive sham leukapheresis of 4 total blood volumes 2 hours later using the COBE SPECTRA Apheresis System MNC Program (version 4.7) (CaridianBCT, Lakewood, CO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To attempt to assess the contribution of circulating monocytes toward alveolar neutrophil recruitment, Barr et al (10) randomized patients to receive leukapheresis of mononuclear cells at intervals after inhaled LPS, followed by a BAL at 9 h. Leukapheresis was successful in significantly reducing, but not eliminating, monocytes (and lymphocytes, platelets) in the blood and BAL but did not significantly reduce circulating or alveolar neutrophil numbers. BAL and serum levels of IL-8, the predominant neutrophil chemokine, and MCP-1, the predominant monocyte chemokine, were similar in the sham and leukapheresis groups (10). The study was limited by a short exposure interval, relatively mild inflammation, incomplete elimination of monocytes, and inability to assess the contribution of resident alveolar macrophages.…”
Section: Macrophage-neutrophil/recruited Macrophagementioning
confidence: 89%
“…For example, it has been recently demonstrated that infiltrating macrophage precursors regulate ongoing neutrophil recruitment and loss of barrier function in ALI associated with gram-negative bacterial infection; therefore, monocyte depletion has been proposed as a potential therapeutic approach. However, monocyte/macrophage depletion might result in loss of important beneficial anti-inflammatory effects of these cells (52,222), and a recent trial failed to prove significant improvement of LPS-induced systemic and pulmonary inflammation in humans after depletion of circulating monocytes (11).…”
Section: Immune Cells and Inflammatory Signaling Pathways In Alimentioning
confidence: 99%